LAND USURPATION - Jusuf Topoljak; Admir Mulahusić (Geodetski Glasnik, 2011)
Work on the topic of "land usurpation," exposes the issue of land usurpation in Bosnia and Herzegovina. Geodesy has a very important role in solving such a complex problem for the whole society. In this paper are given hints of defining and solving the problem of land usurpation.